في هور السناف في محافظة ذي قار, العراق Himantopus himantopus (L.) متطفلة في طيور الكرسوع Tetrameres nouveli (Nematoda: Spirurida) تسجيل جديد للخيطية - هاشم عبد اللهباسم; جبار عبد الركابينهى (University of Thi-Qar Journal of Science, 2019)
Tetrameres nouveli was isolated from the black –winged stilt Himantopus himantopus which was hunted from Sinaph marsh in Thi-Qar province south Iraq dur ing the period April 2014 to March 2015 with prevalence 15.55% and mean intensity of infection 1.42, In the current study, T. nouveli was recorded for the first time in Iraq. عزلت الدودة الخيطية Tetrameres nouveli من طير الكرسوع himantopus Himantopus البالغ عددها 90 طيرا التي تم اصطيادها من هور السناف في محافظة ذي قار جنوب العراق من نيسان 2014 الى اذار 2015. بلغت نسبة الاصابة %15.6 بهذه الخيطية ومعدل شدة اصابة 1.42. وصفت هذه الخيطية وصفا تصنيفيا وقورنت مع الانواع المسجلة في العالم ويعد تسجيلها الاول في العراق .